2009
DOI: 10.1124/jpet.109.151936
|View full text |Cite
|
Sign up to set email alerts
|

The Late Na+ Current (INa) Inhibitor Ranolazine Attenuates Effects of Palmitoyl-L-Carnitine to Increase Late INa and Cause Ventricular Diastolic Dysfunction

Abstract: Palmitoyl-L-carnitine (PC), an ischemic metabolite, causes cellular Na ϩ and Ca 2ϩ overload and cardiac dysfunction. This study determined whether ranolazine [(Ϯ)-1-piperazineacetamide, N-(2,6-dimethylphenyl)-4-[2-hydroxy-3-(2-methoxyphenoxy)propyl]Ϫ] attenuates PC-induced Na ϩ current and ventricular contractile dysfunction of the isolated heart. PC (4 M, 30 min) increased late Na ϩ current by 1034 Ϯ 349% in guinea pig isolated ventricular myocytes; ranolazine (10 M) and tetrodotoxin (TTX, 3 M) significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…However, neither tetrodotoxin nor ranolazine produced any effects on PALCAR-stimulated I MEP found in these cells. Taken together, results from these observations lead us to propose that, in GH 3 cells, PALCAR has a stimulatory effect on I MEP , rather than on late Na + currents [21,28,29. ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, neither tetrodotoxin nor ranolazine produced any effects on PALCAR-stimulated I MEP found in these cells. Taken together, results from these observations lead us to propose that, in GH 3 cells, PALCAR has a stimulatory effect on I MEP , rather than on late Na + currents [21,28,29. ]…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has demonstrated that PALCAR could reduce electrophoretic mobility of erythrocytes [16], elevate intracellular Ca 2+ in vascular endothelial cells [20] and increase the amplitude of late Na + current [21]. Therefore, we further investigated the biophysical properties of I MEP in cells exposed to PALCAR (3 µM) for 2 hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its beneficial effects on LV diastolic function, likely mediated by the prevention of intracellular Ca 2+ overload, have also been shown. 56,57 It may, therefore, be potentially useful for the treatment of HF, also when caused by LV diastolic dysfunction. Beneficial effects on LV remodeling and myocardial fibrosis have also been shown in experimental models.…”
Section: Metabolic Modulatorsmentioning
confidence: 99%
“…In several non-HF animal models, ranolazine reversed diastolic dysfunction (at least partially) during ischaemia and reperfusion, 159,160 in the presence of ischaemic metabolites such as ROS 92 or palmitoylcarnitine, 161 in induced hypertension 162 and in spontaneously hypertensive rats. 163 Interestingly, Lovelock et al 162 suggest that ranolazine can directly modulate myofilament calcium sensitivity besides the well-established ion channel effects.…”
mentioning
confidence: 99%